The use of a medical vibration platform in the treatment of patients with plantar fasciitis - S. I. Dzhadayev; A. V. Dzhadayeva; V. V. Ivanov; M. V. Kovrizhnyh; D. T. Aliev; O. E. Aprishko (National Electronic Information Consortium (NEICON), 2023)
Aim: to evaluate the effect of using a medical vibration platform on the severity of pain, quality of life, functional and anatomical characteristics of the foot and ankle in patients with plantar fasciitis.Materials and methods: the study involved 91 patients with plantar fasciitis, among them 73 (80.2 %) women, 18 (19.8 %) men. The patients were divided into two groups: the main group consisted of 43 patients, the control group - 48 patients. In the main group, standard treatment was performed, including shock wave therapy, kinesio taping, standard exercises in the first week and exercises on a medical vibration platform in the second and third weeks, in the control group, exercises in the second and third weeks were performed with the patient standing on the floor. To assess the dynamics of treatment, a questionnaire was conducted using the VAS, the AOFAS scale, and the SF-36 questionnaire. Instrumental methods of examination included the evaluation of Friedland's podological index, Y-balance test. All parameters were assessed before treatment, after treatment, and 3 months after treatment.Results: the use of exercise therapy on a medical vibration platform in the complex treatment of patients with plantar fasciitis, compared with exercise therapy on the floor, made it possible to statistically significantly reduce the level of pain after treatment (p < 0.05), increase the stability of the feet and ankle joint (p < 0.05 ), and in the long-term period allowed to significantly reduce the level of pain (p <0.05), improve the quality of life (p < 0.05), increase the stability of the foot and ankle joint (p < 0.05).Conclusion: the use of physiotherapy exercises on a medical vibroplatform helps to reduce the level of pain after treatment and after 3 months after treatment, improve the quality of life in the long term, as well as increase the stability of the feet.